ANALISIS POTENSI KEBANGKRUTAN PADA PERUSAHAAN - PERUSAHAAN FARMASI YANG TERDAFTAR DI BEJ DENGAN METODE DISKRIMINAN ALTMAN - -, Herlina (Jurnal Manajemen dan Keuangan, 2009)
Condition a company to influenced by economics condition in country, in the year 1997 Indonesian experiences economy crisis so that happen rupiah rate value depreciation that push the happening of where prices is tall. this matter causess investor quantity that interesting the capital returns and shift it out country. This conditon is of course causess economics condition more wearyer and company in Indonesia experience difficulty in look for capital addition self so that many company that decry to company it because experience finance difficulty or may even exist a part company that experience bankruptcy.Analysis that used to detect condition companies stay in bankrupt condition, gray area and condition not bankrupt by using method altman: zi = 1,2 x1 + 1,4 x2 + 3.3 x3 + 0.6x4 + 1.0 x5. where is value z-score divided in category that is: value z-score < 1,81 experience bankruptcy, value z-score > 2,99 doesnt experience bankruptcy and value z-score present between 1,81-2,99 gray area.Keyword : bankruptcy, method altman, criteria z-score